Physiological and Pathophysiological Responses to Ultramarathon Running in Non-elite Runners - Hoppel, Florian; Calabria, Elisa; Pesta, Dominik; Kantner-Rumplmair, Wilhelm; Gnaiger, Erich; Burtscher, Martin (Frontiers in Physiology, 2019)
Ultramarathon running represents a major physical challenge even for elite athletes. Runners wellbeing may be challenged by fluid and electrolyte disturbances, haemolysis and skeletal muscle damage, decline in hepatic function and kidney injury. We hypothesized that these effects may even be exacerbated in non-elite runners. Physiological, haematological and biochemical parameters of ten males (26 – 45 years, weekly training time 8.5 hours), participating in a mountain ultramarathon (67 km; approximately 4,500 m of total ascent), were determined before (PRE), immediately after finishing the ultramarathon (POST), and 24 hours after the individual finish (REC). Race times of the 8 finishers (2 drop-outs due to hot ambient temperature) varied between 10.4 and 16.1 hours, indicating that study participants represent the entire range of participants in this competition. The following changes in mean values of selected markers for skeletal muscle damage and kidney injury were observed from PRE to POST: creatine kinase (CK) +1289 %, lactate dehydrogenase (LDH) +86.9 %, serum creatinine (CR) + 71.9 %, blood urea nitrogen (BUN) + 95.8 %, and estimated glomerular filtration rate (eGFR) - 44.9 %. Values of CK +1447 %, LDH + 56.1 %, and BUN + 71.4 % remained elevated at REC. White blood cells were increased (+137%) only POST. In conclusion, CK and LDH levels as well as leucocytosis may be considered to be relatively harmless ‘side-effects’ of prolonged running in this group of male subjects with rather moderate ultramarathon experience and training status. However, acute kidney injury may become clinically relevant in this population under the certain conditions, which should be considered by responsible race managers and medical advisors.